229k views
4 votes
Hello, I need assistance with this question. Thank you so much! :) Let ()=2^2−+5. Find (+ℎ) −() / ℎ.

1 Answer

3 votes

The function is given as,


f(x)=2x^2-x+5

It is asked to find the value of the expression,


(f(x+h)-f(x))/(h)

Substitute the values and simplify,


\begin{gathered} =(\mleft\lbrace2(x+h)^2-(x+h)+5\mright\rbrace-(2x^2-x+5))/(h) \\ =(2(x+h)^2-x-h+5-2x^2+x-5)/(h) \\ =\frac{2(x^2+2xh+h^2)^{}-h-2x^2}{h} \end{gathered}

Simplify the expression further,


\begin{gathered} =\frac{2x^2+4xh+2h^2^{}-h-2x^2}{h} \\ =(4xh+2h^2-h)/(h) \\ =\frac{h(4x+2h^{}-1)}{h} \\ =4x+2h^{}-1 \end{gathered}

Thus, the value of the required expression is,


(f(x+h)-f(x))/(h)=4x+2h-1

User Shreyas Shetty
by
5.3k points